Respuesta :

Answer:

[tex]h = \frac{s}{2pir} -r\\[/tex]

Step-by-step explanation:

[tex]s = 2pir(r+h)\\\frac{s}{2pir} = r+h\\h = \frac{s} {2pir} -r[/tex]

To make h subject of the formula ,

Step 1 : Divide both sides by 2pir to isolate (r+h)

Step 2 : Move r to the other side of the equation to isolae h

Answer :

h = s/2pir  -r

Hi1315

Answer:

[tex] h = \frac{s}{2\pi \: r} - r \\ [/tex]

Step-by-step explanation:

[tex]s = 2\pi \: r(r + h) \\ \frac{s}{2\pi \: r} = \frac{2\pi \: r(r + h)}{2\pi \: r} \\ \frac{s}{2\pi \: r} = r + h \\ \frac{s}{2\pi \: r} - r = h\\ [/tex]

hope this helps

brainliest appreciated

good luck! have a nice day!